Roughness of oxide glass subcritical fracture surfaces. Issue 3 (20th October 2017) - Pallares, Gaël; Lechenault, Frédéric; George, Matthieu; Bouchaud, Elisabeth; Ottina, Cédric; Rountree, Cindy L.; Ciccotti, Matteo
Abstract: An original setup combining a very stable loading stage, an atomic force microscope and an environmental chamber, allows to obtain very stable subcritical fracture propagation in oxide glasses under controlled environment, and subsequently to finely characterize the nanometric roughness properties of the crack surfaces. The analysis of the surface roughness is conducted both in terms of the classical root mean square roughness to compare with the literature, and in terms of more physically adequate indicators related to the self‐affine nature of the fracture surfaces. Due to the comparable nanometric scale of the surface roughness, the AFM tip size and the instrumental noise, a special care is devoted to the statistical evaluation of the metrologic properties. The roughness amplitude of several oxide glasses was shown to decrease as a function of the stress intensity factor, to be quite insensitive to the relative humidity and to increase with the degree of heterogeneity of the glass. The results are discussed in terms of several modeling arguments concerning the coupling between crack propagation, material's heterogeneity, crack tip plastic deformation and water diffusion at the crack tip. A synthetic new model is presented combining the predictions of a model by Wiederhorn et al (J Non‐Cryst Solids, 353, 1582‐1591, 2007) on the effect of the material's heterogeneity on the crack tip stresses with the self‐affine nature of the fracture surfaces.